Esterification of Bio-Oil Produced from Sengon (Paraserianthes falcataria) Wood Using Indonesian Natural Zeolites - Kadarwati, Sri; Apriliani, Evalisa; Annisa, Riska Nurfirda; Jumaeri, Jumaeri; Cahyono, Edy; Wahyuni, Sri (International Journal of Renewable Energy Development, 2021)
The bio-oil produced from pyrolysis of woody biomass typically shows unfavourable characteristics such as high acidity, hence it becomes highly corrosive. An upgrading process, e.g., esterification, is necessary to improve the bio-oil quality prior to its use as a transportation fuel. In this work, the bio-oil was produced through a fast pyrolysis of Sengon wood in a fixed-bed pyrolyser at various temperatures. The characteristics (density, viscosity, total acid number, relative concentration of acetic acid, etc.) of the bio-oil were evaluated. The bio-oil with the highest acidity underwent an esterification catalysed by Indonesian natural zeolites at 70 oC for 0-180 min with a ratio of bio-oil to methanol of 1:3. The catalytic performance of the Indonesian natural zeolites during the esterification was investigated. A significant decrease in the total acid number in the bio-oil was observed, indicating the zeolite catalystâ€™s good performance. No significant coke formation (0.002-3.704 wt.%) was obtained during the esterification. An interesting phenomenon was observed; a significant decrease in the total acid number was found in the heating up of the bio-oil in the presence of the catalyst but in the absence of methanol. Possibly, other reactions catalysed by the BrÃ¸nsted and Lewis acids at the zeolite catalyst surface also occurred during the esterification.